Los negocios en la frontera entre Colombia y Venezuela del intercambio comercial a un conflicto social (2015)
Border relations in the «living borders» have been an object of study due to the conditions under which the economy of the borders is developed. Investigations carried out between North Santander and Táchira State border are analyzed, comparing them with the principles of the German (the state-nation) and French (the border area) Schools. Studies of the Chamber of Commerce of Cúcuta are analyzed and discussed. It is concluded that the economy of North Santander is affected more by political and ideological positions than by international trade. Governments continue to ignore the reality of two peoples who share a border region, as it is exposed by the principles of the French School